2016
DOI: 10.1097/md.0000000000005386
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinically important factors on the performance of advanced hydraulic, microprocessor-controlled exo-prosthetic knee joints based on 899 trial fittings

Abstract: The objective of this work is to evaluate whether clinically important factors may predict an individual's capability to utilize the functional benefits provided by an advanced hydraulic, microprocessor-controlled exo-prosthetic knee component.This retrospective cross-sectional cohort analysis investigated the data of above knee amputees captured during routine trial fittings. Prosthetists rated the performance indicators showing the functional benefits of the advanced maneuvering capabilities of the device. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Six publications utilized randomized controlled cross-over design [30,35,36,38,40,41], five publications before-and-after design [37,39,[42][43][44] and one study used a cross-sectional design [34]. In many of the publications, the sample sizes were between 10 and 25, with the exception of one cross-sectional study that reported data of 899 subjects.…”
Section: Study Selection Characteristics and Risk Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…Six publications utilized randomized controlled cross-over design [30,35,36,38,40,41], five publications before-and-after design [37,39,[42][43][44] and one study used a cross-sectional design [34]. In many of the publications, the sample sizes were between 10 and 25, with the exception of one cross-sectional study that reported data of 899 subjects.…”
Section: Study Selection Characteristics and Risk Of Biasmentioning
confidence: 99%
“…Nine articles focused on ambulation, in particular on level walking, stairs and ramps (Table 3) [34][35][36][37][38][39]41,43,44].…”
Section: Ambulationmentioning
confidence: 99%
See 3 more Smart Citations